1994
DOI: 10.1111/j.1748-1716.1994.tb09787.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation of prostaglandins and bradykinin in the effects of angiotensin II and converting enzyme‐inhibition on sympathetic neurotransmission in vivo

Abstract: We investigated the mechanism(s) by which angiotensin converting enzyme (ACE)-inhibition and angiotensin (Ang) II influence peripheral sympathetic neurotransmission in canine gracilis muscle in situ, with alpha-adrenoceptors either intact or irreversibly blocked by phenoxybenzamine. ACE-inhibition by ramiprilat reduced, and subsequent infusion of Ang II (30 ng kg-1 min-1 i.v.) markedly increased arterial plasma Ang-(1-8)octapeptide levels, basal muscle perfusion pressures and mean arterial pressure. Local intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although Chang et al (1995) did not ®nd any such effect in the forearm, Clemson et al (1994) showed, during ®xed forearm blood¯ow, that intrabrachial Ang II infusion facilitated NA release, measured as NA spillover. One possible mechanism for not readily observing an Ang II-facilitated NA release may be due to diffusion limitation for Ang II from the bloodstream to the perivascular nerves (Schwieler et al 1991(Schwieler et al , 1994. Effects of ACE inhibition seem to be even more complex, as several opposing mechanisms are involved, including reduced Ang II formation, bradykinin accumulation and prostaglandin formation (Schwieler et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although Chang et al (1995) did not ®nd any such effect in the forearm, Clemson et al (1994) showed, during ®xed forearm blood¯ow, that intrabrachial Ang II infusion facilitated NA release, measured as NA spillover. One possible mechanism for not readily observing an Ang II-facilitated NA release may be due to diffusion limitation for Ang II from the bloodstream to the perivascular nerves (Schwieler et al 1991(Schwieler et al , 1994. Effects of ACE inhibition seem to be even more complex, as several opposing mechanisms are involved, including reduced Ang II formation, bradykinin accumulation and prostaglandin formation (Schwieler et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In rats with renal hypertension, the antihypertensive effect of capto-pril was intensified by combination with the nonpeptide Ang II receptor antagonist EXP6803 (18) or losartan (19). Since the effects of neither EXP6803 nor losartan were increased by combination with captopril (16,17), the potentiation of BK, prosta glandins, or both, by ACE inhibitors (20,21) mad contribute little to their antihypertensive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Noradrenaline released from the nerve terminals can be estimated by the amount that diffuses into circulation, i.e., spillover. Bradykinin facilitates noradrenaline release in the dog gracilis muscle (Schwieler et al 1994) and the human, guinea pig, and mouse heart (Chulak et al 1998;Hatta et al 1999). These authors reported that this potentiating effect of bradykinin was exerted through the stimulation of B 2 receptors.…”
Section: Discussionmentioning
confidence: 95%
“…Bradykinin facilitates the release of noradrenaline in many tissues in different species through the stimulation of B 2 receptors (Chulak et al 1998;Hatta et al 1999;Schwieler et al 1994). The bradykinin B 2 receptor appears to be responsible for most of the biological actions of bradykinin, whereas the B 1 receptor is usually induced by pathological conditions such as tissue injury or stress (Burch and Kyle 1992).…”
Section: Introductionmentioning
confidence: 98%